PEMANFAATAN WEB INTERAKTIF ECO PATH BERBASIS LITERASI EKONOMI DALAM MENINGKATKAN PEMAHAMAN KONSEP KEGIATAN EKONOMI SISWA SEKOLAH DASAR: STUDI LITERATUR - Wahyu Pandhini, Vinda; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of interactive web-based economic literacy inimproving elementary school students’ understanding of economic activityconcepts. The research employed a literature review method by examining variousrelevant national and international journal articles published between 2020 and2025. Data were collected through documentation techniques and analyzed usingcontent analysis with a thematic synthesis approach. The results indicate thatinteractive web-based learning media can enhance students’ engagement andlearning interest. However, such improvement does not necessarily lead to deeperconceptual understanding without appropriate instructional approaches. On theother hand, economic literacy has been shown to help students understandeconomic concepts more contextually and apply them in daily life. Therefore,integrating interactive web media with economic literacy is considered a promisingstrategy in social studies learning. The use of Eco Path interactive web based oneconomic literacy can create a more engaging, interactive, and meaningfullearning experience. Nevertheless, its implementation still faces severalchallenges, such as limited technological facilities and teachers’ readiness to usedigital tools. Thus, this study is expected to contribute to the development of moreinnovative social studies learning in elementary education.